2023
DOI: 10.3390/pr11061768
|View full text |Cite
|
Sign up to set email alerts
|

Application of Life Cycle of Aeroengine Mainshaft Bearing Based on Digital Twin

Abstract: Aeroengine mainshaft bearings are key components in modern aeroengines, and their main functions are to support the rotation of the main shaft of the aeroengine in harsh environments, such as high temperature, heavy load, high speed and oil break; reduce the friction coefficient during the high-speed rotation of the main shaft; and reliably ensure the rotation accuracy and power transmission of the aeroengine’s main shaft during operation. The manufacture of aeroengine mainshaft bearings requires complex proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The operation and maintenance service system driven by DTs is explained in terms of pattern updating, data application, and system interaction. For instance, this article explores the application of DTs in the operation and maintenance of aviation engines [185], focusing on accurate monitoring, fault diagnosis, performance prediction, control optimization, and other functions. Fu et al [186] identified the time and cost inefficiencies of traditional design, manufacturing, and maintenance processes as inefficient due to their independent operation and management.…”
Section: Product Sustainable Manufacturing and Oandm Managementmentioning
confidence: 99%
“…The operation and maintenance service system driven by DTs is explained in terms of pattern updating, data application, and system interaction. For instance, this article explores the application of DTs in the operation and maintenance of aviation engines [185], focusing on accurate monitoring, fault diagnosis, performance prediction, control optimization, and other functions. Fu et al [186] identified the time and cost inefficiencies of traditional design, manufacturing, and maintenance processes as inefficient due to their independent operation and management.…”
Section: Product Sustainable Manufacturing and Oandm Managementmentioning
confidence: 99%
“…The following are the roles of each of the wind turbine bearings and the main forms of wear. According to the survey data, only 10% of wind power bearings can operate generally during their life span, and 80% of bearing failures are caused by wear [32]. The main factors affecting bearing wear are bearing materials, lubricant selection, and environmental factors [33].…”
Section: Main Forms Of Wear On Wind Power Bearingsmentioning
confidence: 99%
“…Li et al provide an overview of the important manufacturing technologies, production modes, and manufacturing processes based on digital twins in the lifecycle of aeroengine mainshaft bearings, including the metallurgical process, heat treatment process, and grinding process. They present the core technologies and future research directions of the lifecycle of mainshaft bearings based on digital twins and give a defect diagnostic and life analysis of the mainshaft bearings of aeroengines [10]. Kazała et al present the evolution and role of the digital twin concept as one of the key technologies for implementing the Industry 4.0 paradigm in automation and control and emphasized the importance of integration [11].…”
Section: Related Workmentioning
confidence: 99%